Mechanisms on the Injection Conformance Reversion during Polymer Flooding of Offshore Heterogeneous Heavy-Oil Reservoirs - Zhijie Wei; Xiaodong Kang; Yuyang Liu; Hanxu Yang (Geofluids)
Injection conformance reversion commonly observed during polymer flooding in offshore heterogeneous heavy-oil reservoirs weakens the volumetric sweep of polymer solution and compromises its EOR results. To investigate its mechanisms and impact factors, one mathematical model to predicate injection conformance behavior is constructed for heterogeneous reservoirs based on the Buckley-Leverett function. The different suction capability of each layer to polymer solution results in distinct change law of the flow resistance force, which in turn reacts upon the suction capability and creates dynamic redistribution of injection between layers. Conformance reversion takes place when the variation ratio of flow resistance force of different layers tends to be the same. The peak value and scope of conformance reversion decrease and reversion timing is advanced as oil viscosity or permeability contrast increases, or polymer concentration or relative thickness of low permeable layer decreases, which compromises the ability of polymer flooding to improve the volumetric sweep and lower suction of the low permeable layer. The features of offshore polymer flooding tend to make the injection conformance V-type and create low-efficiency circulation of polymer in a high permeable layer more easily. These results can provide guidance to improve the production performance of polymer flooding in offshore heterogeneous heavy-oil reservoirs.